The effect of human resources management on the success of electricity projects (tower transmission) in west Papua province - Ivan Yosefwan Naibaho; Adithya Sudiarno (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The development of electricity facilities and infrastructure plays a vital role in supporting the economic, social, and cultural activities of a nation. The success of construction projects, including transmission towers, can be measured based on the triple constraint, namely correct quality, timely and cost-effective. These three things can be achieved through human resource management. This study aims to measure the influence of human resource management which includes HR planning, project leadership support, organizational structure, and provision of training on the success of electricity projects (transmission towers) in West Papua Province. This study uses a cross-sectional approach to determine the relationship among the variables studied. A partial disaggregation approach with Structure Equation Modeling - Partial Least Square using SmartPLS was carried out to measure the causal relationship among the observed variables. Based on hypothesis testing, it was identified that each variable influences the success of the electricity project, where the provision of training has the greatest influence. Overall the goodness of the model in measuring the relationship between the four factors on project success is shown by the R2 value of 0.880 which is categorized as a strong influence.